Understanding if, How, and Why Women with Prior Spontaneous Preterm Births are Treated with Progestogens: A National Survey of Obstetrician Practice Patterns - Gallagher, Jack R.; Gudeman, Jennifer; Heap, Kylee; Vink, Joy; Carroll, Susan (American Journal of Perinatology Reports, 2018)
Objective In 2017, the Society for Maternal-Fetal Medicine (SMFM) Guideline Committee reaffirmed that 17α-hydroxyprogesterone caproate (17-OHPC) to prevent preterm birth (PTB) is underutilized. We sought to determine what drove progestogen treatment choice of obstetricians managing pregnant women with histories of 1+ singleton spontaneous PTBs (< 37 weeks) who then delivered singleton gestations within the previous 12 months.Subjects We recruited a nationally representative random sample of obstetricians to abstract medical records of study-qualified patients. Of the 423 study-qualified physicians contacted, 358 (85%) participated; 56 (16%) maternal fetal medicine specialists and 302 (84%) general obstetrician/gynecologists (OB/GYNs) extracted data from 991 eligible patient charts.Results Almost three-fourths of patients (73.6%) were treated with 17-OHPC; 18.6% received vaginal progesterone, and 11.8% were not treated. Key drivers of physicians' choice to (1) prescribe branded 17-OHPC were “FDA (Food and Drug Administration) approval” (52% relative influence [RI]) and “SMFM guidelines” (24% RI); (2) prescribe vaginal progesterone were “ease of administration” (32% RI) and “shortened cervix” (16% RI); and (3) not provide prophylaxis were “patient not informed of risk” (35% RI) and “no shortened cervix” (29% RI).Conclusion Study findings support SMFM's contention of continued 17-OHPC underutilization to prevent PTB. Need for additional physician education merits assessment along with appropriate follow-up actions.
Keywords: Spontaneous Preterm Birth (SPTB); prematurity; 17α-hydroxyprogesterone caproate (17-OHPC); progestogen; vaginal progesterone; maternal fetal medicine specialists (MFMs); shortened cervix